Unlock your storybook heart ebook - Lovelace, Amanda (You Are Your Own Fairy Tale, 2022)
"life is not something that can be experienced on a deadline." amanda lovelace, the bestselling & award-winning author of the "women are some kind of magic" poetry series, presents unlock your storybook heart , the third & final installment in her feminist poetry series, "you are your own fairy tale." this is a collection about being so caught up in the fable that is perfectionism that you miss out on your own life. be honest: when was the last time you stopped to take in the everyday enchantment all around you?